Primitive or empowered: representations of Native Americans and COVID-19 in news media. Issue 1 (1st January 2023) - Davidson, Theresa; Miller, Niya Pickett; Day, Bryan
ABSTRACT: Historically, representations of Native Americans in media have tended toward a narrative of a people who are savage at worst, primitive and helpless at best. During the COVID-19 pandemic in the United States, Native Americans were often featured in news coverage about the viral outbreak. Using close textual analysis, this study differentiates between COVID-19 themed news stories featuring Native Americans as told by Native media sources and those offered by non-Native media sources. Though the representations of Native people offered in the reports from non-Native news agencies were generally sympathetic, they upheld longstanding and negative visual tropes of primitiveness and helplessness. Native news sources, however, portrayed Native people as empowered and community oriented. We conclude that when Native people construct their own stories, even in the midst of a devastating pandemic, their narratives further efforts toward Native self-determination and rearticulate the archetypal framing of Native identity in US news coverage.